PENDIDIKAN AGAMA ISLAM DAN PEMBENTUKAN AKHLAK SISWA - Irfan Setia Permana (Pusat Riset dan Inovasi Nasional, 2022)
Islamic religious education has an important role in the formation of student attitudes and personalities, both in the school environment and in the community. Islamic Religious Education emphasizes the formation of Islamic students' personalities, instills understanding and guides students to have honest, disciplined, good character, and beneficial personalities for others. In general, if students' understanding of Islamic Religious Education is high, then their morals, attitudes and behavior can be good, and vice versa. This study aims to determine whether there is an influence of Islamic Religious Education on moral formation at MI Nurul Huda. The benefit of this research is as input for school institutions in seeking and fostering morals. The variables in this study are Islamic Religious Education (X), and moral formation (Y). This research includes quantitative research with a population of 198 students and a sample of 33 students. The data collection method used is documentation and questionnaires, while the data analysis method uses the product moment formula, which is then carried out t test and determination test to test the truth of the hypothesis. The results of the analysis of the data obtained that Islamic religious education learning at MI Nurul Huda has been running effectively and efficiently and has a positive impact on the formation of students' morals.